LOXL1-AS1 promotes cell proliferation in hepatocellular carcinomathrough miR-1224-5p/ITPRIPL2/AKT axis: LOXL1-AS1 promotes cell proliferation in HCC - Chen, Tangen; Zeng, Shuyun; Liu, Quanyuan; Chen, Yufeng; Lu, Junjiang (Cellular and Molecular Biology, 2023)
LncRNA has been validated to be related to different cancers, whereas its regulation mechanism in hepatocellular carcinoma (HCC) is poorly known. In this study, LOXL1-AS1 was overexpressed in HCC cell lines, and LOXL1-AS1 knockdown repressed cell proliferation and stimulated apoptosis in HCC. Besides, the activating role of LOXL1-AS1 in the AKT pathway was also confirmed. Further, miR-1224-5p was sponged by LOXL1-AS1, and overexpression exerted inhibitory function in HCC. Moreover, ITPRIPL2 as amiR-1224-5ptarget gene. Meanwhile, ITPRIPL2 deficiency suppressed HCC cell proliferation. Finally, miR-1224-5p inhibitor reversed the hindering role of LOXL1-AS1 depletion in HCC cell proliferation and AKT pathway, and this rescuing effect was offset by ITPRIPL2 silencing. In summary, LOXL1-AS1 induced cell proliferation and suppresses cell apoptosis in primary HCCvia activating AKT pathway, sponging miR-1224-5p and upregulating ITPRIPL2, which may provide some fresh thoughts for researches about the molecular regulation mechanism of lncRNA in HCC.